Enhanced turbulence driven by mesoscale motions and flow‐topography interaction in the Denmark Strait Overflow plume. Issue 10 (19th October 2016) - Schaffer, Janin; Kanzow, Torsten; Jochumsen, Kerstin; Lackschewitz, Klas; Tippenhauer, Sandra; Zhurbas, Victor M.; Quadfasel, Detlef
Abstract: The Denmark Strait Overflow (DSO) contributes roughly half to the total volume transport of the Nordic overflows. The overflow increases its volume by entraining ambient water as it descends into the subpolar North Atlantic, feeding into the deep branch of the Atlantic Meridional Overturning Circulation. In June 2012, a multiplatform experiment was carried out in the DSO plume on the continental slope off Greenland (180 km downstream of the sill in Denmark Strait), to observe the variability associated with the entrainment of ambient waters into the DSO plume. In this study, we report on two high‐dissipation events captured by an autonomous underwater vehicle (AUV) by horizontal profiling in the interfacial layer between the DSO plume and the ambient water. Strong dissipation of turbulent kinetic energy of O( 10 − 6 ) W kg −1 was associated with enhanced small‐scale temperature variance at wavelengths between 0.05 and 500 m as deduced from a fast‐response thermistor. Isotherm displacement slope spectra reveal a wave number‐dependence characteristic of turbulence in the inertial‐convective subrange ( k 1 / 3 ) at wavelengths between 0.14 and 100 m. The first event captured by the AUV was transient, and occurred near the edge of a bottom‐intensified energetic eddy. Our observations imply that both horizontal advection of warm water and vertical mixing of it into the plume are eddy‐driven and go hand in hand in entraining ambient water into the DSO plume. The second event was found to be a stationary feature on the upstream side of a topographic elevation located in the plume pathway. Flow‐topography interaction is suggested to drive the intense mixing at this site. Key Points: Observations of high turbulent dissipation events in the Denmark Strait Overflow plume using an AUV Baroclinic eddy drives entrainment by both horizontal advection and vertical mixing of warm water Flow‐topography interaction locally induces large rates of vertical mixing